Автоматизація проектування технологічних процесів виготовлення різьбонарізного інструменту на прикладі плашки - Дереза, Олена Олександрівна; Мацулевич, Олександр Євгенович; Вершков, Олександр Олександрович; Чаплінський, Андрій Петрович; Dereza, Olena; Matsulevych, Oleksandr; Vershkov, Oleksandr; Chaplinskyi, Andriy (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: У роботі на прикладі плашок розкрито завдання, з якими стикається інженер під час проєктування різьбонарізного інструменту. Робота дає можливість отримати теоретичні знання про способи та методи виготовлення плашок, види плашок і застосування плашок під час нарізання зовнішньої різьби. Розглянуто процес створення тривимірної моделі матриці методами поверхневого та твердотільного моделювання. Виконано порівняльний аналіз цих методів і наведено практичні рекомендації щодо оптимізації створення моделі матриці засобами PowerShape. Встановлено, що використання систем автоматизованого проєктування під час створення моделей і креслеників різьбонарізного інструменту та складання технологічних процесів їх виготовлення дає змогу істотно спростити, прискорити й автоматизувати роботу інженерно-технічного персоналу підприємства. /// EN: Threaded parts are among the most common in the technological equipment of food and processing enterprises. Thread processing on such parts is a labor-intensive operation among those performed in the mechanical workshops of machine-building enterprises, as well as in the specialized production of screws, bolts, nuts, and pins. CAD allows engineers to significantly reduce the time required to create a model or drawing of a product. In addition, they help to identify errors at the product design stage, rather than during or even after its manufacture. The use of CAD avoids additional material and time costs associated with defects and the need to retool production equipment. The paper uses the example of dies to reveal the tasks that an engineer faces when designing thread cutting tools. The paper provides theoretical knowledge about the methods and techniques of die manufacturing, types of dies, and the use of dies when cutting external threads. The process of creating a three-dimensional model of a die using surface and solid modeling methods is considered. A comparative analysis of these methods is performed and practical recommendations for optimizing the creation of a die model using PowerShape are given. The practical result of the work is the improvement of the technological process of die manufacturing and the creation of a package of technological and design documentation using the means of the automated design system. It was concluded that the use of computer-aided design systems during the creation of models and drawings of thread cutting tools and the compilation of technological processes for their manufacture significantly simplifies, accelerates, and automates the work of the enterprise’s engineering and technical personnel. Power Shape (Delcam) CAD was used to create three-dimensional models of the matrix.
Automation of the design of technological processes for the manufacture of thread cutting tools using the example of a die
Keywords: зовнішня різьба; кругла матриця; універсальний тримач матриці; 3D-модель; оптимальна стратегія; моделювання поверхні; твердотільне моделювання; external thread; round die; universal die holder; 3D-model; optimal strategy; surface modeling; solid modeling